The Effects of Language Competence and Self-regulatory Focus on Intercultural Communication Apprehension: Comparing Japan, China and America - Wang, Lina; Wu, Xiaoyan; Lee, Peter S.; Takai, Jiro (Intercultural Communication Studies, 2026)
The Effects of Language Competence and Self-regulatory Focus on Intercultural Communication Apprehension: Comparing Japan, China and America